2022
DOI: 10.1002/ece3.8604
|View full text |Cite
|
Sign up to set email alerts
|

Humpback whale adult females and calves balance acoustic contact with vocal crypsis during periods of increased separation

Abstract: Acoustic communication is important for animals with dependent young, particularly when they are spatially separated. Maternal humpback whales (Megaptera novaeangliae) use acoustic calling to help minimize the risk of separation from their young calves during migration. These pairs also use acoustic crypsis to minimize detection by males. How they balance a restricted active space with the need to maintain acoustic contact during periods of separation is not yet understood. Here, we analyzed movement metrics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
(94 reference statements)
0
5
0
Order By: Relevance
“…In contrast to competitive groups, escorted mother-calf pairs produced calls less frequently with longer inter-call intervals. The longer ICIs observed in escorted mother-calf pairs were somewhat expected and are likely explained by known mother-calf calling behavior (Indeck et al, 2022) and the group interactions observed during the tag deployments. Although escorts show a preference for females without a calf, as they typically have a greater reproductive potential than maternal females (Craig et al, 2003), they will also prospect among mothers for those that may be in post-partum estrus (Chittleborough, 1958;Pallin et al, 2018).…”
Section: Temporal Patternsmentioning
confidence: 62%
See 3 more Smart Citations
“…In contrast to competitive groups, escorted mother-calf pairs produced calls less frequently with longer inter-call intervals. The longer ICIs observed in escorted mother-calf pairs were somewhat expected and are likely explained by known mother-calf calling behavior (Indeck et al, 2022) and the group interactions observed during the tag deployments. Although escorts show a preference for females without a calf, as they typically have a greater reproductive potential than maternal females (Craig et al, 2003), they will also prospect among mothers for those that may be in post-partum estrus (Chittleborough, 1958;Pallin et al, 2018).…”
Section: Temporal Patternsmentioning
confidence: 62%
“…The addition of one or more escorts to a mother-calf pair increases their energy expenditure (Craig et al, 2014) and could result in injuries to the calf or its separation from its mother (Smultea, 1994). As such, these pairs must balance communication with each other with the potential of being joined by escorts, which is believed to be reflected by lower call rates and levels in these groups (Videsen et al, 2017;Indeck et al, 2022). Nevertheless, these pairs have been found to increase calling rates during periods of increased separation as a means of maintaining acoustic contact while continuing to limit detectability by nearby whales (Indeck et al, 2022).…”
Section: Temporal Patternsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mother–calf pairs of humpback whales ( Megaptera novaeangliae ) and southern right whales ( Eubalaena australis ) infrequently produce calls during diving associated with nursing (Videsen et al 2017; Nielsen et al 2019). Mother–calf pairs also use low-amplitude calls to restrict their acoustic active space (Videsen et al 2017; Nielsen et al 2019; Parks et al 2019), even if they increase the call rate during more frequent separation (Indeck et al 2022). The dominant energy of pulsed call sequences produced by Pacific white-sided dolphins is below 100 kHz and can be easily detected by killer whales, which are one of their predators (Black 2018).…”
Section: Discussionmentioning
confidence: 99%